CRISPR‐BETS: a base‐editing design tool for generating stop codons. Issue 3 (2nd November 2021) - Wu, Yuechao; He, Yao; Sretenovic, Simon; Liu, Shishi; Cheng, Yanhao; Han, Yangshuo; Liu, Guanqing; Bao, Yu; Fang, Qing; Zheng, Xuelian; Zhou, Jianping; Qi, Yiping; et al.
Summary: Cytosine base editors (CBEs) can install a predefined stop codon at the target site, representing a more predictable and neater method for creating genetic knockouts without altering the genome size. Due to the enhanced predictability of the editing outcomes, it is also more efficient to obtain homozygous mutants in the first generation. With the recent advancement of CBEs on improved editing activity, purify and specificity in plants and animals, base editing has become a more appealing technology for generating knockouts. However, there is a lack of design tools that can aid the adoption of CBEs for achieving such a purpose, especially in plants. Here, we developed a user‐friendly design tool named CRISPR‐BETS (base editing to stop), which helps with guide RNA (gRNA) design for introducing stop codons in the protein‐coding genes of interest. We demonstrated in rice and tomato that CRISPR‐BETS is easy‐to‐use, and its generated gRNAs are highly specific and efficient for generating stop codons and obtaining homozygous knockout lines. While we tailored the tool for the plant research community, CRISPR‐BETS can also serve non‐plant species.